(untitled) (Universal International Scientific Journal, 2026)
Creative tourism has emerged as a transformative force within the global tourism industry. Unlike conventional mass tourism, it emphasizes active participation, cultural co-creation, and experiential engagement between tourists and host communities. This paper examines the significance of creative tourism services for the state tourism sector across economic, cultural, and strategic dimensions. The findings demonstrate that creative tourism generates higher per-capita tourist spending, creates sustainable employment, preserves intangible cultural heritage, and enhances destination competitiveness. Policy recommendations are proposed for governments seeking to integrate creative tourism into national tourism strategies.